2012
DOI: 10.1016/j.toxicon.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

General biochemical and immunological characteristics of the venom from Peruvian scorpion Hadruroides lunatus

Abstract: This communication describes the general biochemical properties and some immunological characteristics of the venom from the Peruvian scorpion Hadruroides lunatus, which is the most medically relevant species in Peru. The soluble venom of this scorpion is toxic to mice, the LD₅₀ determined was 0.1 mg/kg and 21.55 mg/kg when the venom was injected intracranial or intraperitoneally, respectively. The soluble venom displayed proteolytic, hyaluronidasic, phospholipasic and cardiotoxic activities. High performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…Similar results reported that human single chain fragment (scFv) recognized toxins of Centruroides noxius Hoffmann and Centruroides suffuses scorpion venom and rescue mice from severe envenomation by whole venom of Centruroides suffuses and Centruroides noxius [65]. Also, polyclonal anti-venom against Hadruroides lunatus displayed cross reactivity with venom from Tityus serrulatus, Centruroides sculpturatus and Androctonus australis hector scorpions [66]. Other study has explained that anti-AmmVIII (Anatoxin from Am venom) antibodies were also found to cross-react towards several of the peptides designed from the AahII structure [67].…”
Section: Discussionsupporting
confidence: 75%
“…Similar results reported that human single chain fragment (scFv) recognized toxins of Centruroides noxius Hoffmann and Centruroides suffuses scorpion venom and rescue mice from severe envenomation by whole venom of Centruroides suffuses and Centruroides noxius [65]. Also, polyclonal anti-venom against Hadruroides lunatus displayed cross reactivity with venom from Tityus serrulatus, Centruroides sculpturatus and Androctonus australis hector scorpions [66]. Other study has explained that anti-AmmVIII (Anatoxin from Am venom) antibodies were also found to cross-react towards several of the peptides designed from the AahII structure [67].…”
Section: Discussionsupporting
confidence: 75%
“…In addition to neurotoxins, scorpion venoms contain enzymes such as hyaluronidase, proteases, and phospholipases. Hyaluronidases are capable of degrading hyaluronic acid (the major component of the extracellular matrix) and are associated with toxin dispersion through tissues (Pessini et al, 2001;Costal-Oliveira et al, 2012;Venancio et al, 2013). Proteases are poorly described and most scorpion species have no detectable protease activity (Venancio et al, 2013;Carmo et al, 2014).…”
Section: Scorpion Venoms and Their Toxinsmentioning
confidence: 99%
“…Scorpion venom toxicity is primarily attributed to neurotoxic peptides with molecular weights ranging between 4.5 and 8 kDa (Borchani et al, 2011a(Borchani et al, ,b, 2013Costal-Oliveira et al, 2012;Venancio et al, 2013). Despite the great diversity of components that comprise scorpion venom, most components are not associated with envenomation; however, these components are immunogenic and therefore are likely to elicit antibody production.…”
Section: Immunization Protocols Using Native Toxic Fractionsmentioning
confidence: 99%
“…Species in this genus appear to be weakly toxic to vertebrates upon peripheral venom injection, as shown in the case of H. ( L. ) lunatus (from Lima, Peru) based on the low lethality (LD50 = 22 mg/kg) of its venom when injected intraperitoneally in mice. H. ( L. ) lunatus venom is, however, highly toxic upon central injection (LD50 = 0.1 mg/kg) [ 83 ]. Although Hadruroides venoms are not lethal to mammals, at least peripherally, they probably contain components able to elicit heart muscle disruption in vertebrates.…”
Section: Annotated List Of Ecuadorian Scorpion Speciesmentioning
confidence: 99%